TOI-2046b, TOI-1181b, and TOI-1516b, three new hot Jupiters from TESS: planets orbiting a young star, a subgiant, and a normal star. Issue 4 (26th May 2022) - Kabáth, Petr; Chaturvedi, Priyanka; MacQueen, Phillip J; Skarka, Marek; Šubjak, Ján; Esposito, Massimilliano; Cochran, William D; Bellomo, Salvatore E; Karjalainen, Raine; Guenther, Eike W; Endl, Michael; Csizmadia, Szilárd; et al.
ABSTRACT: We present the confirmation and characterization of three hot Jupiters, TOI-1181b, TOI-1516b, and TOI-2046b, discovered by the TESS space mission. The reported hot Jupiters have orbital periods between 1.4 and 2.05 d. The masses of the three planets are 1.18 ± 0.14 MJ, 3.16 ± 0.12 MJ, and 2.30 ± 0.28 MJ, for TOI-1181b, TOI-1516b, and TOI-2046b, respectively. The stellar host of TOI-1181b is a F9IV star, whereas TOI-1516b and TOI-2046b orbit F main sequence host stars. The ages of the first two systems are in the range of 2–5 Gyrs. However, TOI-2046 is among the few youngest known planetary systems hosting a hot Jupiter, with an age estimate of 100–400 Myrs. The main instruments used for the radial velocity follow-up of these three planets are located at Ondřejov, Tautenburg, and McDonald Observatory, and all three are mounted on 2–3 m aperture telescopes, demonstrating that mid-aperture telescope networks can play a substantial role in the follow-up of gas giants discovered by TESS and in the future by PLATO .